As diferentes categorias dos hotéis da Rede Accor na cidade de São Paulo: as dimensões avaliativas dos folders do Hotel Formule 1 e do Hotel Sofitel São Paulo - Dias, Rosemary Neves de Sales (2006)
The objective of this work is to examine the folders of two hotels that belong to the Hotel chain Accor: the Formule 1 Hotel and the Sofitel Sao Paulo Hotel an economic and a luxury hotel located in the city of Sao Paulo , in order to verify through the evaluative dimensions in terms of Lemke (1998), the differences of lexicogrammatical choices that accomplish the different languages used by the hotels folders considering the market segment. Having the purpose of examining the evaluative dimensions used by both hotels , the methodology offered by the systemic functional linguistic developed by Halliday (1994; 2004) was chosen, as well as the proposed the Genre and Register Theory proposed by Eggins & Martin (1997). Lemke states that the lexicogrammatical resources enables the expression not only of the ideational meaning as well as the speaker s attitude in relation to his propositions and proposes. Anything we say about the world will carry our point of view about it: if we believe it, it will be usual, expected, important, probable, surprisingly, serious or comprehensible, and these beliefs are transformed into the seven dimensions proposed by him, of this evaluative orientation in relation to the text semantics. At the end of this analysis, the data shows that the evaluative dimensions Importance, Desirability, Warrantability, Expectedness, and not Usuality are present in both folders, while the evaluative dimensions Normativity and not Expectedness are the differences between them